Comparing the efficacy of different antibiotic regimens on osteomyelitis: A network meta-analysis of animal studies - Shi, Xiangwen; Wu, Yipeng; Ni, Haonan; Chen, Xi; Xu, Yongqing (Frontiers in Medicine, 2022)
Background: Despite the surge in the number of antibiotics used to treat preclinical osteomyelitis (OM), their efficacy remains inadequately assessed. Objective: To establish network comparisons on the efficacy of antibiotic regimens on OM in animal studies. Methods: PubMed, Embase, Web of Science, and The Cochrane Library were searched from inception to March 2022 for relevant articles. Odds ratios (ORs) were generated for dichotomous variants and the standard mean difference (SMD) was calculated for constant variables. The predominant outcomes were the effective rate of sterility, namely sterility rates, as well as the bacterial counts at the end of experiments, including minimum inhibition concentration and minimum bactericidal concentration. All the meta-analyses and network meta-analyses were performed using STATA MP 16.0. This study was registered in the International Prospective Register of Systematic Reviews (PROSPERO; no. CRD42022316544). Results: A total of 28 eligible studies with 1,488 animals were included for data analysis, including 13 antibiotic regimens. Regarding the effective rate of sterility, glycopeptides (GLY), linezolid (LIN), rifampicin (RIF)+β-Lactam, and β-Lactam showed significant efficacy compared with the placebo (OR: 0.01-0.08). For radiological grade, only RIF+GLY (SMD: -5.92, 95% confidence interval: -11.65 to -0.19) showed significant efficacy compared with the placebo. As for reducing bacterial counts, fosfomycin, tigecycline, GLY, LIN, RIF, RIF+β-Lactam, RIF+GLY, aminoglycosides and clindamycin showed significant efficacy compared with placebo (SMD: -6.32 to -2.62). Moreover, the bone concentrations of GLY were higher 1 hour after administration and the higher blood concentrations were higher after 1 and 4 hours compared with the other antibiotics. Conclusions: Multiple antibiotic regimens showed significant efficacy in animals with OM, including increasing effective rates of sterility, reducing bacterial counts and lowering radiological scores. Among them, RIF+GLY was the most promising treatment regimen owing to its optimal efficacy. Based on the preclinical studies included in our meta-analysis, head-to-head clinical randomized controlled trials are required to confirm these findings in humans.